Uji Ekstrak N-Heksan Daun Kirinyuh (Chromolaena Odorata L.) Terhadap Model Hewan Luka Bakar Derajat IIA - Wan Tisya Muhaira; Luthvia Luthvia; Ningrum Wahyuni; Indah Afriwanty Simatupang; Bayu Ariatama (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Chromolaena odorata referred to as Kirinyuh leaves, contains tannins, phenols, flavonoids, saponins, and steroids, which possess antibacterial properties against several pathogenic bacteria in humans, including Staphylococcus aureus, Escherichia coli, and Candida albicans. This investigation aimed to assess the moderate efficacy of the N-Hexan cream derived from Chromolaena odorata L. against Grade IIA burns in male Wistar rats. The research employed a laboratory experimental approach, encompassing the creation of an N-hexane extract from Chromolaena odorata L. and the formulation of various burn cream preparations of 20%, 25%, and 30% concentrations. Multiple tests are conducted: organoleptic assessment, homogeneity evaluation, and testing of pH, spreadability, adhesion, and burn. The research analysis employed a one-way ANOVA followed by the LSD test. The most effective dose for hastening burn wound healing is a 30% concentration of n-Hexan extract, resulting an average healing rate of 79%. The ANOVA test outcomes revealed a significant value of 0.000 (≤ 0.05) indicating a statistically significant difference in burn wound healing by day 21. The findings indicate that the N-Hexan extract from Chromolaena odorata L, exhibits a capacity to expedite the healing of burn wounds in male Wistar rats, as evidenced in both the 25% and the 30% concentration group.